2020
DOI: 10.1002/admt.201900981
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Functionally Graded Materials and Structures via Additive Manufacturing: From Multi‐Scale Design to Versatile Functional Properties

Abstract: Functionally graded materials (FGMs) and functionally graded structures (FGSs) are special types of advanced composites with peculiar features and advantages. This article reviews the design criteria of functionally graded additive manufacturing (FGAM), which is capable of fabricating gradient components with versatile functional properties. Conventional geometrical‐based design concepts have limited potential for FGAM and multi‐scale design concepts (from geometrical patterning to microstructural design) are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
135
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 329 publications
(137 citation statements)
references
References 225 publications
(344 reference statements)
0
135
0
2
Order By: Relevance
“…Functionally graded materials prevent the drastic transition of mechanical properties at interfaces and provide a smooth transition of properties. Thus, functionally graded materials mitigate stress concentrations over interfaces and provide durability, especially as load-bearing supports [ 89 ]. Functional gradients are additionally useful in medical applications since they provide a complex structural diversity of bioinspired gradients and facilitate more control over fluid flow, mass transport, biodegradation, and mechanical properties, such as stiffness, strength, and hardness, throughout a designed structure, which are beneficial for biomedical implants [ 90 ].…”
Section: Design Strategiesmentioning
confidence: 99%
“…Functionally graded materials prevent the drastic transition of mechanical properties at interfaces and provide a smooth transition of properties. Thus, functionally graded materials mitigate stress concentrations over interfaces and provide durability, especially as load-bearing supports [ 89 ]. Functional gradients are additionally useful in medical applications since they provide a complex structural diversity of bioinspired gradients and facilitate more control over fluid flow, mass transport, biodegradation, and mechanical properties, such as stiffness, strength, and hardness, throughout a designed structure, which are beneficial for biomedical implants [ 90 ].…”
Section: Design Strategiesmentioning
confidence: 99%
“…FGMs can be utilized in various areas, including biomedicine, structural parts, aviation, thermal management, energyabsorbing systems, optoelectronic, electromagnetic interference shielding (EMI), and even geological models that can analyze earthquakes and natural landslide disasters (Li Y. et al, 2020). The FGM concept can also be used in 4-D printing by the functionally graded additive manufacturing (FGAM) concept in which a single AM process incorporates the gradational mixing of materials in order to construct freeform geometries with changing properties within one component (Sudarmadji et al, 2011;Pei et al, 2017).…”
Section: Future Scenerymentioning
confidence: 99%
“…In particular, the 316 L SS key properties, i.e., strength and corrosion resistance, were retained and enhanced further through the HIP treatment and thus to tailor the properties of the hybrid components and make them suitable for several applications. 316 L SS is a very well-known biomaterial for hip and knee replacement, due to its high strength, corrosion and wear resistance, and beneficial cell proliferation that can be subsequently enhanced through various coating techniques [9,67,68]. It has been reported that in non-HIP samples, exposed pores can hold contaminants that can leave defects during plating and harbour bacteria in medical applications.…”
Section: Application Areas Of Hybrid 316 L Stainless Steelmentioning
confidence: 99%